The Effect of Playing Online Vocabulary Games and Motivation on Student’s Vocabulary Mastery in Insan Utama Junior High School Pekanbaru - herlianisyah lubis (Jurusan Tarbiyah dan Pendidikan, 2020)
The importance of vocabulary mastery given communicate well between students and teacher in the classroom and learning active. Without vocabulary impossible use English language as communication Burton, and vocabulary total number of the word making up the language, master the fundamental grammatical pattern of language Hornby. In relation to the theoretical ideas, vocabulary is the key factor to ensure that production (receptive vocabulary and productive vocabulary) to get vocabulary as the key factor need a motivation in proces learning. With playing online game it is hoped students have a motivation in learning foreign language especially English subject. Playing online game can relax for students because young learners like games. Based on Ashraf (2014:290), gamers became more intersted in playing online and wished to achieve better result. Students more interactive and motivating and effective in vocabulary. It is the researchers’ reasone to choose online game for up grading students motivation and increase students’ vocabulary. Study got significant impact and change for the students learning, motivation and vocabulary.